VALUASI EKONOMI EKOSISTEM HUTAN MANGROVE DI NEGERI PASSO KOTA AMBON - Willem Talakua (LPPM Universitas Pekalongan, 2013)
Extensive mangrove forest in coastal area of Ambon city reached 64,316 acres, with shoreline length is 8,951 m based on mangrove forest, that the existing is spread in 13 villages, one of them is Passo village that has mangrove area 27.8761 acres. The existing of mangrove forest in Passo or in the other area in Ambon city not only gives physical benefit and economy but also biological benefit, but often misused by the local community is by doing over exploitation that can destruct the mangrove ecosystem. This case is caused by the low awareness the local community about how important mangrove forest and also the lowness of appreciation of mangrove forest potentials as economic asset. The research is aimed to analyze the economic value of the mangrove forest in coastal area of Passo village, Ambon city. Data collection is done by observation, interview and also from secondary data. Data analyzing data based on natural resources concept or environment concept according to Suparmoko (2002), and Reuitenbeek (1991). Research result shows the extensive of Passo’s mangrove forest is 27,8761 acres, and produces total economic value of 185.800.570 rupiah/year consist of direct benefit value 11.449.423 rupiah/year, indirect benefit value 160.379.819 rupiah/year, existing benefit 9.804.125 rupiah/year, and choice benefit 4.167.203 rupiah/year. Keywords : economic valuation, mangrove forest ecosystem, Passo village.